The global regulatory framework for decarbonisation: 3x3 starting points for the reform of global economic governance - Clara Brandi; Dominique Bruhn; Nannette Lindenberg (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
Mitigating climate change and limiting global warming to no more than 2°C require a fast and radical transformation of politics, the economy and society. Worldwide emissions of greenhouse gases need to fall to zero by 2100. Action needs to be even faster in the case of carbon dioxide (CO2), which is primarily released in the burning of fossil fuels. According to the Intergovernmental Panel on Climate Change (IPCC), global CO2 emissions need to reach zero by 2070 at the latest. In other words, the global economy needs to be completely decarbonised by then. The sustainable development goals (SDGs) of Agenda 2030 underscore the significance of this task. The decarbonisation of our economic activity is dependent not only on the international climate regime, but also the regulatory framework for the world economy, i.e. global economic governance. In addition to progress made in the context of the UN Framework Convention on Climate Change (UNFCCC) and the fundamental acknowledgment of all states of the need to tackle climate change in the scope of Agenda 2030 there are currently numerous initiatives that give cause for optimism – not least the commitment of the G7 states to the decarbonisation of the global economy and manifold climate actions of actors such as cities, churches and companies. However, further reaching reforms of global economic framework conditions are necessary if a fundamental transformation is to be achieved. We therefore propose 3x3 starting points: 3 areas of action, each with 3 key aspects. Of particular importance for the decarbonisation of the global economy are (A) adequate pricing, (B) a suitable body of regulations for international trade and investment and (C) the appropriate configuration of the financial markets. (A) To achieve correct pricing it is necessary to (i) introduce a global carbon price, (ii) continue to remove subsidies for fossil fuels, and (iii) extend the system of payments for ecosystem services. (B) A suitable regulatory framework for international trade and investment includes (i) climate-friendly multilateral trade rules under the aegis of the World Trade Organization (WTO), (ii) the promotion of plurilateral agreements for the liberalisation of environmental goods and services and (iii) increased focus on the right to regulate in terms of environmental aspects in bilateral and regional trade and investment agreements. (C) In addition to the establishment of global funds such as the Green Climate Fund (GCF), the area of global financial governance has three starting points in particular: (i) regulation of financial markets, (ii) green guidelines for investment decisions and (iii) guarantee instruments for green investments. For all reform measures there is a need to identify potential win-win constellations that offer co-benefits to as many participants as possible. In addition, attention should also be paid to trade-offs and political economy. This includes the question of which actors are in favour of the necessary measures, which resist them and why and how coalitions of change can be formed and reinforced.
Keywords: 330; Handel und Investitionen; Internationales Finanzsystem